Public policy to reduce antibiotic resistance - Frimodt-Møller, Niels (Henry Stewart Talks, 2010)
Factors of importance for low antibiotic use, Consumption of systemic antibacterials, Resistant isolates in Europe, Change in fluoroquinolone use, Correlation between antibiotic consumption and resistance, Cefuroxim and ciprofloxacin use and resistance against E. coli, Selection, Public reimbursement of antimicrobials, Tetracycline use, Ciprofloxacin use in general practice, Role of pharmacies, Consumption of medicines without prescription, Antibiotic treatment guidelines, Institute for rational pharmacotherapy, Monitoring of anti-microbial use, National antibiotic barometer, Microbiology services, GPs must pursue a rational antibiotic policy, Registration of antibiotic use, Educating the public, Self-medication, Public policy to reduce antibiotic resistance
Reviewed at 2015/07/24